2019
DOI: 10.1139/cjz-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and apoptosis in starved and refedNeocaridina davidi(Crustacea, Malacostraca) midgut

Abstract: Adult specimens of the freshwater shrimp Neocaridina davidi Bouvier, 1904 (Crustacea) were starved for 7, 14, and 21 days. Specimens from the first and second experimental group were collected for the studies. The majority of animals starved for 21 days died. Additionally, some specimens from each group were refed for 4, 7, and 14 days. The epithelium of the midgut, which is composed of the intestine and hepatopancreas, was analyzed. While the epithelium of the intestine is formed by D- and R-cells, the epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Until now, many works related to the physiological, biochemical and histological changes during starvation of crustaceans have been published [3][4][5][6][7]. The results presented in this works are directly related to the earlier works describing ultrastructural changes in the midgut of N. davidi during starvation [8][9][10]. In the cited works, the average time of starvation after which regeneration of shrimps is impossible has been obtained.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Until now, many works related to the physiological, biochemical and histological changes during starvation of crustaceans have been published [3][4][5][6][7]. The results presented in this works are directly related to the earlier works describing ultrastructural changes in the midgut of N. davidi during starvation [8][9][10]. In the cited works, the average time of starvation after which regeneration of shrimps is impossible has been obtained.…”
Section: Introductionmentioning
confidence: 66%
“…Other studies indicated that the intensity of autophagy and apoptosis has also increased, which may indicate that it is a part of survival strategy. Moreover, after 14 days of refeeding, the apoptosis level was found to be lower than in the control group [9]. Starvation is causing oxidative stress in living organisms.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore the processes related to the survival strategy during exposure to starvation are observed primarily in this organ. Long-term periods of starvation can cause numerous changes at the physiological, biochemical and molecular levels which lead to increased ability to survive (Wilczek et al, 2014;Lipovšek et al, , 2018Włodarczyk et al, 2017Włodarczyk et al, , 2019. Starvation can affect and damage many organelles, including the mitochondria (Ratcliffe and King, 1969;Włodarczyk et al, 2017), which are responsible for e.g.…”
Section: Introductionmentioning
confidence: 99%